1992
DOI: 10.1113/jphysiol.1992.sp019153
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous sarcoplasmic reticulum calcium release and extrusion from bovine, not porcine, coronary artery smooth muscle.

Abstract: SUMMARY1. We tested the hypothesis that the Ca2+-loaded sarcoplasmic reticulum (SR) of coronary artery smooth muscle spontaneously releases Ca2+ preferentially toward the sarcolemma to be extruded from the cell without increasing the average free myoplasmic [Ca2+] (Caim) concentration. 9. The results support the hypothesis that the SR spontaneously releases Ca2+ to be extruded from the cell. The species variation in the results may provide insight into the role of the SR as a Ca2' buffer barrier, which is suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 41 publications
8
75
0
Order By: Relevance
“…In the rabbit IVC, continuous unloading of the superficial SR to the extracellular space, involving coupling of SR release channels to the forward mode NCX, permits buffering of Ca 2ϩ influx to continue (51). Such spontaneous and preferential unloading of the SR toward the PM has also been observed in the bovine coronary artery (65). In support of this postulate, Fig.…”
Section: Mechanism Of Wavelike [Ca 2؉ ]I Oscillationssupporting
confidence: 68%
“…In the rabbit IVC, continuous unloading of the superficial SR to the extracellular space, involving coupling of SR release channels to the forward mode NCX, permits buffering of Ca 2ϩ influx to continue (51). Such spontaneous and preferential unloading of the SR toward the PM has also been observed in the bovine coronary artery (65). In support of this postulate, Fig.…”
Section: Mechanism Of Wavelike [Ca 2؉ ]I Oscillationssupporting
confidence: 68%
“…Also, [Ca 2ϩ ] cyt reported by FFP-18 reaches levels about 3 times higher than that reported by fura-2. In freshly isolated bovine, porcine, and guinea pig coronary artery smooth muscle cells (Stehno-Bittel and Sturek, 1992;Ganitkevich, 1996), the K Ca -mediated current was used to report subplasmalemmal [Ca 2ϩ ] cyt . It was monitored simultaneously with fura-2 "global" [Ca 2ϩ ] cyt signals.…”
Section: Pharmacological Modulation Of Smooth Muscle Srmentioning
confidence: 99%
“…This large cell surface/cell volume ratio in smooth muscle favors exquisite regulation of cell surface processes by instantaneous changes in intracellular composition, such as the regulation by (presumably) spontaneously released Ca 2ϩ from the SR, known as "Ca 2ϩ sparks", of Ca 2ϩ -activated K ϩ (K Ca ) (see reviews by Wellman and Nelson, 2003) and chloride (Cl Ca ) channels (Kotlikoff and Wang, 1998). Earlier studies by Benham and Bolton (1986) and by Stehno-Bittel and Sturek (1992) lead to the suggestion that the frequently observed spontaneous K ϩ currents recorded in smooth muscle (Benham and Bolton, 1986;Ohya et al, 1987;Desilets et al, 1989;Hume and Leblanc, 1989) occur in regions of the cell where the SR and the PM are closely apposed. This Ca 2ϩ release from the SR, presumed to occur spontaneously, occurs in close proximity to K Ca channels and reaches a [Ca 2ϩ ] cyt of 10 to 100 M and an average size of 13 m 2 , which covers ϳ1% of the 1300 m 2 of the smooth muscle membrane .…”
mentioning
confidence: 99%
“…Ten years ago, we demonstrated significant non-uniformity in the distribution of Ca 2+ in quiescent vascular smooth muscle cells using patch-clamp and microscopy techniques [16,17]. Since then, several reports have demonstrated that non-uniform Ca 2+ distribution exists in smooth muscle cells in a variety of conditions [1,18,19].…”
Section: Introductionmentioning
confidence: 99%